Some limitations of evaluating dual-polarized MIMO channel capacity - О.О. Мартинчук; Г.М. Зубрицький; Лі Сюань; О.О. Мартинчук (Системи обробки інформації, 2020)
This article discusses possible bandwidth limitations of a radio access channel using MIMO technology with polarization-orthogonal channels, or dual polarization channels. The main attention is paid to the presence of cross-polarization isolation between channels, or cross-polarization relation, or Cross Polar Discrimination. The indicated ratio is determined mainly by the design features of the antennas. It is proposed to choose antennas with the minimum required values of cross-polarization ratio, which limit a given channel bandwidth.